2021
DOI: 10.1111/jcal.12537
|View full text |Cite
|
Sign up to set email alerts
|

Integrating modified WebQuest activities for programming learning

Abstract: The study designed WebQuest activities and explored the learning performance of learners to understand the suitability of using WebQuest in a college programming course. The study modified the processes of WebQuest based on social constructivism and scaffolding learning, and included programming tasks such as debugging practice to encourage learners to develop their problem‐solving abilities. The WebQuest learning sheets include the following four parts, introduction, task, resources and evaluation, and the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
1
6
0
1
Order By: Relevance
“…This learning method fosters positive motivation and critical thinking. The results of this study confirm the inferences drawn from the previous studies that employing technological devices in the Chinese learning process enhances the learners' motivation and their enjoyment when studying (Seitkazy et al, 2016;Chen, 2019;Zheng, 2018, Wang, 2021. By learning through WebQuest lessons, the learners managed their own learning process with no time limitations (Mitsikopoulou, 2014;Liu, Huang & Wosinski, 2017;Zeng & Fu, 2019).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This learning method fosters positive motivation and critical thinking. The results of this study confirm the inferences drawn from the previous studies that employing technological devices in the Chinese learning process enhances the learners' motivation and their enjoyment when studying (Seitkazy et al, 2016;Chen, 2019;Zheng, 2018, Wang, 2021. By learning through WebQuest lessons, the learners managed their own learning process with no time limitations (Mitsikopoulou, 2014;Liu, Huang & Wosinski, 2017;Zeng & Fu, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…Their findings revealed that after implementing the WebQuest-based critical thinking programme, the students' thinking skills improved, especially in terms of their vocabulary when expressing their opinions. Similarly, Wang (2021) used WebQuest for the purpose of supporting the students to actively participate in the information technology (IT) classroom. They found that the students engaged with their learning more and that their problem-solving abilities increased.…”
Section: What Is Webquest?mentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that there is a huge amount of modern information and simulation resources that can be used in teaching specialized subjects to foreign students. However, Wang (2021) notes in his study that such resources are insufficient to study professional vocabulary.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of programming learning are manifested in two ways: improving program writing skills [9,13] and promoting problem-solving skills [10,23]. In practical task scenarios, programming usually encounters two types of problems: syntactic errors (i.e., syntax rules of the programming language) and semantic errors (i.e., program logic or algorithms).…”
Section: Programming Learningmentioning
confidence: 99%